CERMINAN LEGITIMASI PEMERINTAHAN ISLAM DI MASA PANDEMI - Khalik, Subehan (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
This paper is an attempt to make a comparison between the Islamic government and the Jokowi government in dealing with a pandemic. By using descriptive explanatory methods to solve the problem of popular support to the government through the granting of legitimacy to power. The long journey of the Islamic government in the historical stage illustrates the solidity and expertise of the rulers to win the sympathy of the people. The Prophet’s time was the beginning of the Islamic government in which the Prophet played two functions; as head of the State and holder of the highest religious authority. The two forces were united in the Prophet until his death and continued by his companions afterward, but the pattern of the Prophet’s power was no longer the same as his companions. When friends hold the reins of power, they must try to win the sympathy of the people to get the legitimacy of power. That is why religious languages are always maintained for generations to maximize the function of the authorities as holders of religious authority. Facing a pandemic, two things must always unite, namely; the full authority of the government and religious authority to get the legitimacy of power. The purpose of writing is to provide input to the government to win the hearts of the majority Muslim population to gain the legitimacy of their power and be a strong grip of the government is facing the co-19 pandemic